A Judge For Criminal Justice Decisions In Consideration Of Criminal Acts Of Murder (Case Study No. 299/PID.B/2013/PN.GST) - Elfiana Hulu (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2021)
Abstract: At Gunungsitoli District Court Decision Number 299/Pid.B/2013/PN.Gst), the defendant was sentenced to 12 years in prison for committing a joint murder. In this verdict, the defendant clearly acted as the main perpetrator or intellectual of the murder and the defendant also threatened one of the witnesses with the aim of making the witness participate in the murder. So the act of the defendant should be punished more severely in accordance with the provisions of the criminal law. Based on these descriptions, the researcher interested in conducting research entitle “Pertimbangan Hakim Terhadap Putusan Pemidanaan Pada Tindak Pidana Pembunuhan (Studi Putusan Nomor 299/Pid.B/2013/PN.Gst).” Based on the results and discussion, it is concluded that the Judge’s consideration in the conviction of the crime of murder (case study decision number 299 / Pid.B / 2013 / PN.Gst), the judge has a non-juridical basis for consideration, namely where the defendant is polite in court, has never been convicted, and the defendant acknowledged and regretted his actions, while the juridical consideration was that based on the facts of the trial, the defendant legally committed the crime of murder. So the judge should have sent a conviction to the defendant as stipulated in Article 340 Jo 55 paragraph (1) of the Criminal Code. Keywords: Judges Considerations, Criminal Decisions, Murder Criminal Act